2017
DOI: 10.5194/hess-21-1279-2017
|View full text |Cite
|
Sign up to set email alerts
|

Extending flood forecasting lead time in a large watershed by coupling WRF QPF with a distributed hydrological model

Abstract: Abstract. Long lead time flood forecasting is very important for large watershed flood mitigation as it provides more time for flood warning and emergency responses. The latest numerical weather forecast model could provide 1-15-day quantitative precipitation forecasting products in grid format, and by coupling this product with a distributed hydrological model could produce long lead time watershed flood forecasting products. This paper studied the feasibility of coupling the Liuxihe model with the Weather Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Furthermore, the revised factor could be preserved as an empirical value for future flood prediction in the LKRB. The Liuxihe model proposed by Yangbo Chen (Chen, 2009) of Sun Yat-Sen University, China, is employed as the fully distributed hydrological model in this study, which is a physically based distributed hydrological model (PBDHM) mainly for catchment flood simulation and prediction (Chen et al, 2016Li et al, 2017). The Liuxihe model earned its name by being the first successful application in the Liuxihe catchment, Guangdong Province, China.…”
Section: The Post-processed Persiann-ccs Qpesmentioning
confidence: 99%
“…Furthermore, the revised factor could be preserved as an empirical value for future flood prediction in the LKRB. The Liuxihe model proposed by Yangbo Chen (Chen, 2009) of Sun Yat-Sen University, China, is employed as the fully distributed hydrological model in this study, which is a physically based distributed hydrological model (PBDHM) mainly for catchment flood simulation and prediction (Chen et al, 2016Li et al, 2017). The Liuxihe model earned its name by being the first successful application in the Liuxihe catchment, Guangdong Province, China.…”
Section: The Post-processed Persiann-ccs Qpesmentioning
confidence: 99%
“…Moreover, the effect of forecasting lead-time on the accuracy of predicted values showed that the accuracy of the predictions and the forecast capabilities significantly improved by decreasing the forecasting lead-time [19]. The comparison of different lead-times for WRF model forecast showed that increasing the lead-time caused the overestimation of rainfall in the Liujiang River basin and decreased the forecast accuracy [20].…”
Section: Introductionmentioning
confidence: 98%
“…Prediction of catchment response and the flooding processes induced by rainfall is another essential component in an effective fluvial flood forecasting system, which may involve the use of a wide variety of hydrological or hydraulic/hydrodynamic models (Campolo et al, 1999; Chau et al, 2005; Chiang et al, 2007; Nayak et al, 2005). In addition to those overly simplified statistical approaches, hydrological models are commonly used to predict flooding at a catchment scale (Blöschl et al, 2008; Garrote & Bras, 1995; J. Li et al, 2017; Liu et al, 2005). The output of a hydrological model is typically time series of flow rate in the river channels.…”
Section: Introductionmentioning
confidence: 99%